Employee Performance and the Effects of Compensation, Motivation, and Job Satisfaction - Harun Samsuddin; Andi Tenry Sose; Darmawati Manda; Rusydi Fauzan; Zarkasi Zarkasi (Jurnal Mirai Management, 2023)
One of the after-sales services offered by the Yamaha corporation, Yamaha One Day Service, offers maintenance and repair services for the customer's Yamaha unit on-site. One of the key components for effective unit functioning is the maximum performance of the Yamaha employees that work onsite maintenance in the Bandung region. This study aims to investigate the effects of pay on performance, pay on job satisfaction, pay on performance through job satisfaction, pay on performance, pay on performance through job satisfaction, pay on performance through job satisfaction, pay on performance, pay on performance through job satisfaction. A sample of the workforce was taken using the census method, and there are currently 39 respondents who work in the Bandung region. The analysis makes use of path analysis with SMART PLS. According to the results, 1) compensation has a positive but not statistically significant impact on performance, 2) compensation has a positive and significant impact on job satisfaction, 3) compensation has a positive and significant impact on performance via the variable job satisfaction, and 4) motivation has a positive but not statistically significant impact on performance. SAY KEY : Compensation, Motivation, Satisfaction Work, Performance employee